Analysis of Sterilizer Oil Losses through Variations in Pressure and Boiling Time with Dominated Fresh Fruit Bunch Overripe Fraction - Rengga Arnalis Renjani; Boy Doli Panjaitan; Nabillah Nissya Fadhillah; Harsunu Purwoto (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2024)
The problem is that not all FFBs processed daily are more than 90% ripe fruit, causing the yield not to reach the target. This study aims to analyze condensate oil losses from non-standard FFB quality (FFB overripe as much as 25-26%) against time and pressure variations in the sterilizer. The observed indicators include oil losses, moisture content, and non-oil solids (NOS). The study was conducted in 2 stages; the first stage was to test the length of boiling time for each peak stew. The second stage is divided into two pressure variations treatments at each stew's peak. The quantitative presented data is analyzed using simple statistics. All data analyzed statistically is presented in graphical form to visualize the data distribution. In overripe FFB conditions, as much as 25-26% shows that the three best times for peak 1 are 10 minutes with a pressure of 1.0 kg/cm2, peak 2 is 15 minutes with a pressure of 1.5 kg/cm2, and peak 3 is 65 minutes with pressure 3.1 kg/cm2. he best boiling based on the right boiling time to achieve the lowest oil losses is 90–100 minutes in one boiling cycle. If a boiling cycle of 90-100 minutes is carried out, the oil losses achieved are 0.78-0.98%. The longer the boiling process is under FFB overripe, the more oil comes out of the mesocarp and finally comes out mixed with condensate water.